2018
DOI: 10.1074/jbc.ra118.003756
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the evolution of nidovirus endoribonuclease based on the finding that nsp15 from porcine Deltacoronavirus functions as a dimer

Abstract: Nidovirus endoribonucleases (NendoUs) include nonstructural protein 15 (nsp15) from coronaviruses and nsp11 from arteriviruses, both of which have been reported to participate in the viral replication process and in the evasion of the host immune system. Results from a previous study of coronaviruses SARS-CoV, HCoV-229E, and MHV nsp15 indicate that it mainly forms a functional hexamer, whereas nsp11 from the arterivirus PRRSV is a dimer. Here, we found that porcine (PDCoV) nsp15 primarily exists as dimers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…The function of the coronaviral endoribonuclease has been shown to be important for evading multiple host dsRNA sensors, including melanoma differentiation-associated protein 5 (MDA5), protein kinase R (PKR) and 2′-5′-oligoadenylate synthetase (OAS) [reviewed in ( Deng and Baker, 2018 )]. Sequence alignment from all four CoV genera and structural analysis showed that δ-CoV EnU contains the key residues that are required for endoribonuclease activity ( Deng and Baker, 2018 ; Zheng et al, 2018 ). As shown for EndoUs of mouse hepatitis virus, human coronavirus 229E, SARS-CoV-2, and PEDV, PDCoV EndoU may also interfere with host innate immunity ( Deng et al, 2017 , 2019 ; Kindler et al, 2017 ; Yuen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The function of the coronaviral endoribonuclease has been shown to be important for evading multiple host dsRNA sensors, including melanoma differentiation-associated protein 5 (MDA5), protein kinase R (PKR) and 2′-5′-oligoadenylate synthetase (OAS) [reviewed in ( Deng and Baker, 2018 )]. Sequence alignment from all four CoV genera and structural analysis showed that δ-CoV EnU contains the key residues that are required for endoribonuclease activity ( Deng and Baker, 2018 ; Zheng et al, 2018 ). As shown for EndoUs of mouse hepatitis virus, human coronavirus 229E, SARS-CoV-2, and PEDV, PDCoV EndoU may also interfere with host innate immunity ( Deng et al, 2017 , 2019 ; Kindler et al, 2017 ; Yuen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Each Nsp15 protomer is composed of three domains including an N-terminal domain (ND) that is important for oligomerization, a variable middle domain (MD), and a C-terminal endonuclease (endoU) domain that shares homology with other endoU enzymes (Fig. 1a ) 17 . Nsp15 is only active as a hexamer, but the molecular requirement for Nsp15 oligomerization is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that PDCoV nsp15 has evolved a novel mechanism for the antagonism of IFN production in an endoribonuclease activity-independent manner, distinct from that reported previously for the inhibition of IFN-β production by other CoV nsp15 s or arterivirus nsp11 s. The reason that results in these differences remains unclear. In terms of structure, the active form of endoribonuclease from PDCoV nsp15 is different from that of other CoV nsp15 s. PDCoV nsp15 is a mixture of dimers and monomers, while the nsp15 s of SARS-CoV, MHV, HCoV-229E, as well as MERS-CoV, function as a hexamer (Ricagno et al, 2006;Xu et al, 2006;Zhang et al, 2018;Zheng et al, 2018). Whether these structure differences result in different mechanisms used to antagonize IFN production remains further study.…”
Section: Discussionmentioning
confidence: 98%
“…Previous study has demonstrated that PDCoV nsp15 His219 (H219), H234, and Lys269 (K269) are the critical sites for its endoribonuclease activity (Zheng et al, 2018). To investigate whether or not PDCoV nsp15 mutants lacking endoribonuclease activity possess the ability to antagonize IFN-β production.…”
Section: Pdcov Nsp15 Inhibits Ifn-β Production Independently Of Its Ementioning
confidence: 99%